Incidence of invasive pneumococcal disease in 5-15 year old children with and without comorbidities in Germany after the introduction of PCV13: Implications for vaccinating children with comorbidities - Weinberger, Raphael; Falkenhorst, Gerhard; Bogdan, Christian; Van Der Linden, Mark; Imoehl, Matthias; Von Kries, Rildiger (Vaccine, 2015)
To describe the burden of suffering from IPD in children aged 5-15 years with and without comorbidities up to 5 years after the introduction of PCV13 in Germany and to identify the potential benefit for PCV13 and PPV23 vaccination.The surveillance of IPD for children <16 years was based on two independently reporting sources: active surveillance in pediatric hospitals and a laboratory-based sentinel surveillance system.IPD with cultural detection of pneumococci at a physiologically sterile site in children from 2010 to 2014 in Germany. Incidence was estimated by capture-recapture analysis with stratification by absence/presence of comorbidities. Coverage of the observed serotypes by different vaccines was assessed.142 (Capture recapture-corrected: 437) cases were reported: 72.5% were healthy children and 27.5% had a comorbidity. The incidence of IPD related to children with comorbidities was 0.2 per 100,000. One third of these cases had serotypes not included in either vaccine. The remaining cases might benefit from pneumococcal vaccination but one third of all cases was not vaccinated. The additional potential benefit of PPV23 compared to PCV13 with respect to coverage was 10%.The incidence of IPD in children with comorbidities in Germany is low. Pneumococcal vaccination uptake in children with comorbidities should be increased, although only about two-thirds of the cases might be preventable by presently available vaccines.
EVALuna2:7678